Hell is for heroes [videorecording (DVD)] - McQueen, Steve, 1930-1980; Darin, Bobby; Parker, Fess; Siegel, Don, 1912-1991 (Widescreen DVD collection., 2001)
It's autumn 1944 along the Siegfried Line -- a hopelessly out-numbered army squad tries to fool the Germans into thinking they represent a great Allied Task Force until reinforcements arrive.